FEASIBILITY TEST OF CRITICAL THINKING SKILLS ON HIGH SCHOOL STUDENTS IN STATIC FLUID MATERIAL - Amelia Sitompul; Wawan Bunawan (INPAFI (Inovasi Pembelajaran Fisika), 2021)
This study aims to develop critical thinking instruments in high school students with static fluid material. The development model used in this study is the Analysis-Design-Develop-Implement-Evaluate (ADDIE) learning design model. The subjects of this study were 90 students of XI MIA class in MAN 1 of Medan. The research methods used were interviews, tests, questionnaires, and documentation. The developed test instrument consisted of a grid of test questions, questions, answer sheets, answer keys and scoring guidelines, and guidelines for interpretation of results. Validity test used is content validity test. The results of the validity test by three expert validators showed that the critical thinking test instrument developed was valid. The reliability of the questions developed was 0.82, which means a reliable test item. There are 15 questions, and 12 questions are used for limited scale tests, 10 questions are used for broad scale tests.Keywords: critical thinking skill, multiple choice, static fluid.